Consumer Behavior Analysis in Retail Settings of Palmira: Impact of the Retail Laboratory on Display Strategies - Márquez Mejía, Brian Mauricio
This article focuses on the detailed characterization of consumer behavior in retail establishments in Palmira, Valle del Cauca, using Eye tracking technology. Based on a theoretical framework that includes models such as AIDA (Attention, Interest, Desire and Action) and contemporary merchandising theories, the study examines how eye tracking can offer a deeper and more accurate view of consumer purchasing and attention patterns. The methodology used is mixed, combining quantitative data obtained through eye tracking with qualitative analysis of the perceptions and preferences of merchandisers, floor managers, supervisors, administrators and point of sale managers, as well as retail consumers. The results highlight the critical relevance of product layout and display strategies in influencing purchasing decisions. Eye tracking allows us to identify patterns of attention, showing that products located at eye level and in strategic areas of the shelves receive greater attention. It is concluded that placement strategies must be carefully designed to maximize the visibility and attraction of the product. Future lines of research suggest exploring how other advanced technologies, such as artificial intelligence and big data analytics, could complement consumer behavior analysis and further optimize marketing strategies in the retail sector.